Survival Analysis for Patients with ALK Rearrangement‐Positive Non‐Small Cell Lung Cancer and a Poor Performance Status Treated with Alectinib: Updated Results of Lung Oncology Group in Kyushu 1401. (30th October 2019) - Iwama, Eiji; Goto, Yasushi; Murakami, Haruyasu; Tsumura, Shinsuke; Sakashita, Hiroyuki; Mori, Yoshiaki; Nakagaki, Noriaki; Fujita, Yuka; Seike, Masahiro; Bessho, Akihiro; Ono, Manabu; Nishitsuji, Masaru; et al.
Abstract: Lessons Learned: Alectinib confers a pronounced survival benefit in patients with ALK rearrangement‐positive non‐small cell lung cancer and a poor performance status. Survival benefit of alectinib for patients with a poor performance status was consistent regardless of the presence of central nervous system metastases. Background: We previously reported a marked objective response rate (ORR) and safety for alectinib treatment in patients with ALK rearrangement‐positive non‐small cell lung cancer (NSCLC) and a poor performance status (PS) in the Lung Oncology Group in Kyushu (LOGiK) 1401 study. It remained unclear, however, whether alectinib might also confer a long‐term survival benefit in such patients. Methods: Eighteen patients with ALK rearrangement‐positive advanced NSCLC and a PS of 2, 3, or 4 ( n = 12, 5, and 1, respectively) were enrolled in LOGiK1401 between September 2014 and December 2015 and received alectinib. We have now updated the survival data for the study. Results: The median follow‐up time for all patients was 27.3 months. The median progression‐free survival (PFS) was 16.2 months (95% confidence interval [CI], 7.1–30.8 months), and the median survival time (MST) and the 3‐year overall survival rate were 30.3 months (95% CI, 11.5 months to not reached) and 43.8% (95% CI, 20.8–64.7%), respectively. This survival benefit was similarly manifest in patients with a PS of 2 (MST, 20.5 months) and those with a PS of ≥3 (MST, not reached). PFS did not differ between patients with or without central nervous system (CNS) metastases at baseline (median of 17.5 and 16.2 months, respectively, p = .886). Conclusion: Alectinib showed a pronounced survival benefit for patients with ALK rearrangement‐positive NSCLC and a poor PS regardless of the presence of CNS metastases, a patient population for which chemotherapy is not indicated.